TwinF interface inhibitor FP802 prevents retinal ganglion cell loss in a mouse model of amyotrophic lateral sclerosis - Wang, Yumeng; Yan, Jing; Williams-Fairless, Sarah K.; Fairless, Richard; Bading, Hilmar (Acta Neuropathologica Communications, 2024)
Motor neuron loss is well recognized in amyotrophic lateral sclerosis (ALS), but research on retinal ganglion cells (RGCs) is limited. Ocular symptoms are generally not considered classic ALS symptoms, although RGCs and spinal motor neurons share certain cell pathologies, including hallmark signs of glutamate neurotoxicity, which may be triggered by activation of extrasynaptic NMDA receptors (NMDARs). To explore potential novel strategies to prevent ALS-associated death of RGCs, we utilized inhibition of the TwinF interface, a new pharmacological principle that detoxifies extrasynaptic NMDARs by disrupting the NMDAR/TRPM4 death signaling complex. Using the ALS mouse model SOD1G93A, we found that the small molecule TwinF interface inhibitor FP802 prevents the loss of RGCs, improves pattern electroretinogram (pERG) performance, increases the retinal expression of Bdnf, and restores the retinal expression of the immediate early genes, Inhibin beta A and Npas4. Thus, FP802 not only prevents, as recently described, death of spinal motor neurons in SOD1G93A mice, but it also mitigates ALS-associated retinal damage. TwinF interface inhibitors have great potential for alleviating neuro-ophthalmologic symptoms in ALS patients and offer a promising new avenue for therapeutic intervention.
Gesehen am 25.02.2025